(untitled) (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Avulsion fractures of the calcaneal tuberosity remains rare; they usually caused by forced ankle dorsiflexion; direct trauma occur infrequently; it must be treated immediately; to avoid the skin necrosis of the posterior heel; the treatment approach is of interest in this rare injury and the operative management is based on a review of the literature. ; Non operative treatment is classically associated with bad results. Hence the surgical intervention is generally the treatment of choice. The authors report two cases of unusual avulsion fractures of the calcaneal tuberosity treated by open reduction and internal fixation with a good functional result.